Front Cover: Synthesis, Characterization, and Cytotoxicity of a Reactive Platinum(IV) Monotrifluoromethyl Complex (Eur. J. Inorg. Chem. 3/2023). Issue 3 (21st December 2022) - Liu, Yanpeng; Yao, Houzong; Tse, Man‐Kit; Chen, Shu; Yiu, Shek‐Man; Zhu, Guangyu
Abstract : The Front Cover shows a Pt(IV) monotrifluoromethyl complex containing a reactive chloride ligand trans to the trifluoromethyl ligand. This Pt(IV) complex is very stable in water but displays high reactivity towards various substrates including buffer components and 5'‐dGMP. The study of the reaction mechanism reveals that this Pt(IV) complex reacts with phosphate via the SN 2 nucleophilic substitution pathway, which is different from the mechanism of action of Pt(II) drugs. The Pt(IV) monotrifluoromethyl complex is cytotoxic to human ovarian cancer cells. More information can be found in the Research Article by G. Zhu and co‐workers .